SUNTIK RAYAP UPAYA PELESTARIAN BAHAN PUSTAKA DI PERPUSTAKAAN UIN RADEN FATAH PALEMBANG - Nurmalina Nurmalina (UIN Imam Bonjol Padang, 2019)
Library material damage in the library occurs due to various factors including factors characteristic of library materials, enviromental factors and biota factors. This research was conducted with the aim to find out the factors causing damage to library materials at UIN Raden Fatah Palembang library and find solutions to overcome them. This research is a qualitative descriptive study, using verbal data si words, sentences and images. Sources of data in this study are person, place and paper. The person who is the source of data in this study is the coordinator in the field of circulation services. Place is the central library of UIN Raden Fatah Palembang. Whreas paper is library documents such as damaged data racks adn book colellection. Data collection techniques used in this study were obseravtion, interviews and documentation. The result of this study indicate that damage to shelves and library collections is caused by termites. For damaged collections removed from the shelves and repaired according to the level of damage if possible and replace wooden shelves with iron shelves. While the termites are eradicated by injection and spraying cabinets and termite nests with anti-terminate chemical into the holes that have been drilled on the floor around the library.